2022
DOI: 10.1088/1741-2552/ac823d
|View full text |Cite
|
Sign up to set email alerts
|

Neural decoding from surface high-density EMG signals: influence of anatomy and synchronization on the number of identified motor units

Abstract: Objective. High-density surface electromyography (HD-sEMG) allows the reliable identification of individual motor unit (MU) action potentials. Despite the accuracy in decomposition, there is a large variability in the number of identified MUs across individuals and exerted forces. Here we present a systematic investigation of the anatomical and neural factors that determine this variability. Approach. We investigated factors of influence on HD-sEMG decomposition, such as synchronization of MU discharges, distr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Within this work, we show that the decomposition goodness for both EMG and MMG is negatively correlated with the thickness of subcutaneous fat tissue as well as the contraction intensity. This is consistent with decomposition results from experimentally measured surface EMG signals (e.g., de Oliveira et al, 2022, Del Vecchio et al, 2020, Farina et al, 2008, even if other factors may play a role (Taylor et al, 2022).…”
Section: Insights On Muscle-induced Bio-electromagnetic Fieldssupporting
confidence: 89%
“…Within this work, we show that the decomposition goodness for both EMG and MMG is negatively correlated with the thickness of subcutaneous fat tissue as well as the contraction intensity. This is consistent with decomposition results from experimentally measured surface EMG signals (e.g., de Oliveira et al, 2022, Del Vecchio et al, 2020, Farina et al, 2008, even if other factors may play a role (Taylor et al, 2022).…”
Section: Insights On Muscle-induced Bio-electromagnetic Fieldssupporting
confidence: 89%
“…More older adults were recruited due to the potential for a smaller motor unit yield due to age‐related motor neurone loss (denervation and reinnervation cycle) (Hepple & Rice, 2016 ). Thicker fat tissue between the muscle and electrodes was also expected, which could potentially reduce the motor unit yield (Oliveira et al., 2022 ). The participants had no history of neurological disorders, were free of lower limb musculoskeletal injuries, and were not taking medications that could influence the monoaminergic system, including serotonin or noradrenaline modulators (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies, however, have shown similar physiological differences between RT and UT individuals regardless of sex (56). The additional challenge is employing HDsEMG recordings in a female population which typically results in a substantially smaller yield of discerned MU firings (57), possibly because of sex differences in adipose tissue that acts as a biological low-pass filter (58), although the direct comparison of sexes and factors associated with differences in MU yield remains to be investigated. This decomposition challenge should be addressed in future studies examining neuromuscular characteristics of RT and UT individuals of both sexes (59).…”
Section: Discussionmentioning
confidence: 99%